GEOGRAPHICAL ANALYSIS OF SIZE AND PATTERN OF VILLAGES IN RAMPUR DISTRICT: जनपद रामपुर में ग्रामों का आकार एवं प्रतिरूप का भौगोलिक विश्लेषण - Kumar, Satayendra; Rawal, L.B.; Singh, Saudan (International Journal of Research -GRANTHAALAYAH, 2020)
Habitat geography is the new sprout branch of human geography. Both rural domicile and urban domicile are the two main strands of geography. Habitat geography studies the effect of physical and cultural considerations on man-made habitats, just as human geography describes the environment and human interactions. Human occupancy is the focal center within and around which man builds his culture. Human occupancy refers to all the natural elements and man-made structures that the process of habitat establishes, habitat boundaries that separate them from each other, spatial relationships that link them to both adjacent and remote areas, and The institute, which has been set up to maintain its social and cultural, economic, political and other importance. अधिवास भूगोल मानव भूगोल की नवीन अंकुरित शाखा है। ग्रामीण अधिवास और नगरीय अधिवास दोनों ही अधिवास भूगोल के दो प्रमुख तन्तु है। अधिवास भूगोल मानव द्वारा निर्मित आवासों पर भौतिक तथा सांस्कृतिक बातों के प्रभाव का अध्ययन करता है, ठीक उसी भाॅंति जिस प्रकार मानव भूगोल वातावरण तथा मानव के पारस्परिक सम्बन्धों का विष्लेशण करता है। मानव अधिवास वह नाभीय केन्द्र है जिनके भीतर व जिसके चारों ओर मानव अपनी संस्कृति का निर्माण करता है। मानव अधिवास उन सभी प्राकृतिक तत्वों और मानव निर्मित संरचनाओं की ओर संकेत करता है जो बसाव स्थापन की प्रक्रिया आवासों का स्थापन, मानवीय सीमाएँ जो उनको एक-दूसरे से अलग करती है, स्थानिक सम्बन्ध जो उसको समीपवर्ती तथा दूरस्थ दोनों ही क्षेत्रों से जोड़ते है तथा वह संस्थान सामाजिक सांस्कृतिक, आर्थिक, राजनीतिक तथा अन्य जिनका स्थापन उसे संचालित व प्रधानता बनाये रखने के लिए किया गया है।